GUIDELINES FOR IMPROVING OF INDUSTRYEDUCATION INTEGRATION PRIVATE UNIVERSITIES IN GUANGDONG PROVINCE - Jiancong, Chen; Suteeniran, Niran; Dejhome, Pachara; Setkajorn, Sarayut; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2024)
This research aims to develop guidelines for improving the integration of private university industry education in Guangdong Province. Using a survey research model, the population consisted of 291 administrators in private universities in Guangdong Province. The interview group consisted of 20 senior administrators from private universities in Guangdong Province, including 15 qualified experts, to assess the appropriateness and feasibility of implementing the guidelines. Don't choose a specific type. The research tool is a 5-level estimation questionnaire with a confidence level of .93. Statistics used for data analysis include percentages, averages, and standard deviations. and content analysis. The results of the research found that 1) The current situation of educational integration of private universities in 5 areas is at a high level. Consider educational results from the highest to the lowest level: the highest average is ability development, followed by teacher resource management. management mechanism financial management and science and technology is the lowest average. 2) Guidelines for improving the integration of private university industry education in Guangdong Province combined with interviews. The researcher proposes 1) Improving Teacher resource management, 2) Supporting financial management, 3) Complete management mechanisms, 4) Developing complete abilities, and 5) Strengthening science and technology, a total of 32 approaches from the analysis of effectiveness and the feasibility of the proposed approach in this study revealed that the effectiveness and feasibility of the approach were high. The executives play an important role in formulating development strategies towards successful goals under the provision of freedom of work, encouragement and systematic monitoring. Promote participation, planning and joint evaluation under the quality team.